2017
DOI: 10.1155/2017/2740963
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptors as a Biological Pathway for the Anti-Inflammatory and Beneficial Effects of Low Frequency Low Energy Pulsed Electromagnetic Fields

Abstract: Several studies explored the biological effects of low frequency low energy pulsed electromagnetic fields (PEMFs) on human body reporting different functional changes. Much research activity has focused on the mechanisms of interaction between PEMFs and membrane receptors such as the involvement of adenosine receptors (ARs). In particular, PEMF exposure mediates a significant upregulation of A2A and A3ARs expressed in various cells or tissues involving a reduction in most of the proinflammatory cytokines. Of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 83 publications
1
48
0
Order By: Relevance
“…PEMF stimulation has been previously shown by others to exert anti-inflammatory effects by activating adenosine receptors [41,44], while modulating intracellular calcium and activating the mechanotransduction FAK/Rho GTPases signaling pathways to induce MSC migration [67]. PEMF exposure was also shown to activate a calcium-mitochondrial axis stimulating mitochondrial respiration and promoting both mitochondriogenesis and myogenesis as well as reducing basal apoptosis and increasing telomere length via a process of adaptive magnetic mitohormesis [35].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PEMF stimulation has been previously shown by others to exert anti-inflammatory effects by activating adenosine receptors [41,44], while modulating intracellular calcium and activating the mechanotransduction FAK/Rho GTPases signaling pathways to induce MSC migration [67]. PEMF exposure was also shown to activate a calcium-mitochondrial axis stimulating mitochondrial respiration and promoting both mitochondriogenesis and myogenesis as well as reducing basal apoptosis and increasing telomere length via a process of adaptive magnetic mitohormesis [35].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the expression and paracrine action of these growth factors was also demonstrated in electrically driven MSC chondrogenesis [39]. PEMF exposure has also been shown to exert anti-inflammatory effects by upregulating A2A and A3ARs, thereby mitigating the expression of pro-inflammatory cytokines [40,41]. This is supported by studies showing PEMF inhibition of the PGE2 and cycloxigenase-2 (COX-2) pathways, reducing the expression of pro-inflammatory cytokines (IL-6, IL-8) while augmenting anti-inflammatory factors (cAMP, IL-10) in synovial fibroblasts from bovine and osteoarthritic patients [42][43][44].…”
Section: Introductionmentioning
confidence: 98%
“…Refractory seizure activity can be treated with a ketogenic diet, which works in part by increasing A1AR-mediated inhibition of seizure activity (Masino et al, 2011) Electroconvulsive therapy as a treatment for mood disorders has been reported to act through the release of ATP to indirectly raise adenosine concentrations and activate the brain A1AR leading to its antidepressant effect (van Calker and Biber, 2005). Curiously, pulsating electromagnetic fields (PEMFs) were found to upregulate adenosinergic signaling in cancer and inflammation models (Varani et al, 2017;Vincenzi et al, 2018).…”
Section: Other Unanticipated Interactions With Arsmentioning
confidence: 99%
“…Vincenzi et al [] showed that 75 Hz 2.5 mT PEMFs upregulated the expression of A 2a and A 3 AR adenosine receptors in hFOB 1.19 osteoblastic cells, as well as in other cell models, as summarized by their review [Varani et al, ]. These authors observed that PEMFs significantly increased the density and functionality of adenosine receptors while leaving their ligand affinity unchanged.…”
Section: Effects Of Pemfs On Osteoblastsmentioning
confidence: 99%